The Role of Human Resource Management in Achieving Outstanding Performance Through Individual Culture: An Analytical Study of a Sample of Iraqi Ministry of Interior Officers - Haider Sabah; Nidhal Mgadmi (Migration Letters, 2023)
The objective of this research is to address a limited knowledge gap pertaining to the research variables. This will be accomplished by pursuing several objectives, which include gaining a comprehensive understanding of the concept of Human Resource Management (HRM), examining its five dimensions (attraction and recruitment, training and development, employee motivation, wages and rewards, performance evaluation), comprehending the notion of exceptional employee performance within the study environment, and acknowledging the concept of individual culture within the study environment. Furthermore, the objective is to comprehend the correlation and influence among the variables under investigation, and to quantify them utilizing suitable statistical techniques. The research employed a descriptive-analytical technique, drawing upon prior studies and relevant theoretical literature pertaining to the issue of investigation. The selection of this approach was based on its suitability for the present study, since it effectively examines the data, processes, and resultant impacts in a realistic manner. The data was acquired by conducting a survey targeting personnel of the Iraqi Ministry of Interior, with the objective of examining the impact of Human Resource Management (HRM) on attaining exceptional performance through individual culture. The analysis employed various statistical approaches, such as arithmetic means, tests of validity and reliability, t-tests, and structural equation modeling (SEM), to examine the data obtained from the questionnaire. The study made use of two prominent statistical software tools, namely SPSS and AMOS. The statistical software package SPSS was employed for the purpose of analyzing quantitative data, computing means, and conducting tests to assess the validity and reliability of the data. In contrast, the AMOS program was employed to examine the structural interdependencies among various variables and statistical models.